Bio-nanocomposite edible coatings based on arrowroot starch/cellulose nanocrystals/carnauba wax nanoemulsion containing essential oils to preserve quality and improve shelf life of strawberry - Oliveira Filho, Josemar Gonçalves de [UNESP]; Albiero, Beatriz Regina; Calisto, Ítalo Henrique; Bertolo, Mirella Romanelli Vicente; Oldoni, Fernanda Campos Alencar [UNESP]; Egea, Mariana Buranelo; Bogusz Junior, Stanislau; Azeredo, Henriette Monteiro Cordeiro de; Ferreira, Marcos David (Elsevier, 2022)
This study investigated the effects of bio-nanocomposite coatings developed using arrowroot starch (AA), cellulose nanocrystals (CNC), carnauba wax nanoemulsion (CWN), and Cymbopogon martinii and Mentha spicata essential oils (CEO and MEO, respectively) on the physicochemical, microbiological, bioactive, antioxidant, and aromatic characteristics of strawberries cv. ‘Oso Grande’ in refrigerated storage for 12 days. The coatings improved the shelf life and stability of strawberries, minimizing their weight loss (2.6–3.9 %), as well as changes in color and texture (except for those coated with CEO), titratable acidity, pH, soluble solids, anthocyanins, phenolic compounds, ascorbic acid content, and antioxidant activity compared with uncoated control strawberries. The bio-nanocomposite coatings containing MEO and CEO also exhibited antimicrobial activity, reduced visible fungal deterioration (40–60 %), and reduced microbial load (3.59–4.03 log CFU g−1 for mesophilic aerobic bacteria and 4.45–5.22 log CFU g−1 for fungi and yeast) during storage. They also significantly reduced the severity of decay caused by inoculation with Botrytis cinerea or Rhizopus stolonifer. The coatings altered the volatile profile of the fruits during storage, decreasing aldehyde and alcohol concentrations and increasing ester concentrations. Thus, these bio-nanocomposite coatings, especially those containing MEO, can be used as antimicrobial coating materials to preserve the post-harvest quality of fresh strawberries.
Keywords: Active coatings; Nano reinforcement; Spearmint